Protocol for a systematic review of sarcopenia in older adults with type 2 diabetes mellitus and its association with increased risk of mortality - Whaikid, Phatcharaphon; Piaseu, Noppawan; Souza, Anita (Frontiers in Medicine, 2025)
BackgroundSarcopenia and type 2 diabetes mellitus (T2DM) are prevalent health conditions that significantly impact mortality risk, particularly among older adults. While both conditions have been individually associated with increased mortality, limited evidence exists regarding their combined effect, and no prior systematic review has synthesized this association specifically among older adults with T2DM. This study aims to examine the association between sarcopenia and all-cause mortality in older adults with T2DM. It seeks to evaluate whether this relationship varies by population characteristics, sarcopenia definitions, and follow-up duration.MethodsWe will conduct a comprehensive literature search using databases such as PubMed, Scopus, CINAHL, and Embase to identify studies exploring the relationship between sarcopenia and all-cause mortality in older adults with T2DM from January 1, 2014, to September 1, 2024. Two authors will independently screen all eligible clinical studies. Statistical analyses will be conducted using JBI SUMARI software.ResultsPreliminary findings will indicate the overall prevalence and mortality rate among older adults with sarcopenia and T2DM. By consolidating findings from diverse studies, this meta-analysis will provide clearer insights into how sarcopenia and T2DM interact to affect mortality risk.ConclusionUnderstanding the relationship between sarcopenia and T2DM is crucial leading to developing effective interventions to reduce mortality risk and improve the quality of life in older adults. Addressing this important research gap will contribute to better healthcare practices and outcomes.